TREN RISET SUPERVISI AKADEMIK KEPALA SEKOLAH DI SEKOLAH DASAR : SISTEMATIK LITERATUR REVIEW - Sri Widyawati; Hitta Alfi Muhimmah; Hendratno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the context of primary education, the role of school principals as academic supervisors is critical to improving the quality of learning and student learning outcomes. This study aims to identify research trends related to academic supervision by principals in primary schools and its effect on teacher motivation and performance. The method used in this study is Systematic Literature Review (SLR), which involves searching and analyzing 13 scientific articles from the google scholar database within the time span of 2019 to 2024. The results showed that effective academic supervision, which involves data-driven and collaborative approaches, can improve teacher performance and student learning outcomes. In addition, the use of technology in academic supervision was shown to speed up the monitoring and evaluation process, allowing for faster feedback to teachers. The study also found that principals who apply distributive leadership can improve the efficiency of supervision by involving other staff in the process. The conclusion of this study emphasizes that to improve the quality of education in primary schools, principals need to be further trained in academic supervision skills and adequate policy support should be provided. Further research is needed to explore more specific academic supervision practices at the primary school level in order to understand the different dynamics compared to other levels of education Keywords : Academic Supervision, Principle, teacher performance